Regulasi Kecerdasan Buatan (AI) dalam Perspektif Hukum Indonesia: Menimbang Kesenjangan, Risiko Keamanan Nasional, dan Cetak Biru Tata Kelola yang Berdaulat - Gilang Rizki Aji Putra; Sri Ajeng Murni Cahyani Putri (BULETIN ADALAH, 2025)
Artificial Intelligence (AI) is a general-purpose technology that is transforming economic, political, and security systems. However, Indonesia lacks a specific AI regulatory framework and still relies on outdated legal instruments. This article analyzes Indonesia’s current AI governance, identifies regulatory gaps, and proposes improvements for rights protection and national security. Using normative legal research with conceptual and comparative approaches based on the EU AI Act, the study finds that the absence of an AI law creates legal uncertainty and increases risks of algorithmic discrimination, surveillance, and AI-related crimes. Existing draft regulations remain non-binding and insufficient. The article concludes that a risk-based AI law and independent oversight are urgently needed. Keywords: Artificial Intelligence, AI Regulation, Algorithmic Discrimination, Digital Surveillance, Governance.